ASUPAN CAIRAN DAN STATUS HIDRASI MEMPENGARUHI PROFIL TEKANAN DARAH PADA ATLET SEPAKBOLA REMAJA - Penggalih, Mirza Hapsari Sakti Titis; Juffrie, Mohammad; Sudargo, Toto; Sofro, Zaenal Muttaqien (PERSATUAN AHLI GIZI INDONESIA, 2016)
Athletes tend move with a higher intensity and longer than a normal healthy human being. High intensity exercise coupled with high environmental temperature leads to an increase in body temperature and increased risk of dehydration. Given that the negative impact of dehydration on cardiac function and termoregulatori at practice, then the fluid intake and hydration status were closely related to the stability of the heart to maintain the performance. The study was carried out in 4 months. It was an observational study with a longitudinal cohort design. The total subjects in this study were 131 teenage footballers. Statistical testing using multiple regression analysis. The study showed that fluid intake and hydration status, and change in body weight of the subjects before and after exercise provided significant effect on systolic blood pressure (P<0.05). Every increased in fluid intake and changes in body weight lowers blood pressure by 0.408 systolic mmHg, and increased in fluid intake and changes in percent body weight increase in blood pressure of 2.762 mmHg. The study concluded that intake of fluids as dehydration status protects athletes due to fluid loss. It was because the activities becomes an important key to re-establish the systolic blood pressure. The more frequent training, the more increasingly athletes being exposed to dehydration, so that the systolic blood pressure would continue to increase. It was recommended that rehydration for athletes - who experienced a weight loss of more than 2% - should be done immediately after exercise, asuming that 1 kg of body weigth loss could be replaced by at least 1 litter of fluid.